The Influence of Product Packaging and Product Conformity on Consumer Purchase Intention: Evidence from PT. Alam Jaya Wirasentosa Sibolga Branch - Marbun, Yuliana Susanti Adelina (Devitara Innovations, 2025)
This study aims to analyze the effect of product packaging and product conformity on consumer purchase intention at PT. Alam Jaya Wirasentosa Sibolga Branch. The research employed a quantitative approach with an explanatory research design. The population consisted of 398 consumers, with a sample of 100 respondents selected proportionally. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that simultaneously product packaging and product conformity have a positive and significant effect on purchase intention, with an F-value of 39.965 and a significance level of 0.000 < 0.05. Partially, product packaging has a significant effect (t-value 3.074; sig 0.003 < 0.05), while product conformity shows a more dominant influence (t-value 6.847; sig 0.000 < 0.05). The coefficient of determination (R²) of 0.452 indicates that 45.2% of the variation in purchase intention can be explained by the two independent variables. The regression model obtained is Y = 5.299 + 0.259X₁ + 0.560X₂. These findings suggest that improving packaging quality and aligning products with market needs can enhance consumer purchase intention.